Deciphering microaggressions: Advancing a theoretical framework for scholarly inquiry - Sean McCallaghan; Renier Steyn (Interdisciplinary Journal of Management Sciences, 2025)
Microaggressions (MA) are said to be a subtle everyday form of discrimination where, in some cases, the perpetrators are not even aware that they are acting in a discriminatory manner. There seems to be interest from scholars regarding MA, with several authors attempting to understand the underlying theory that explains MA behaviour. The main objective of this study was to critically review and systematically organise the literature that sought to explain the theoretical underpinning of MA. This was necessary for structuring future studies so that they would contribute to the existing body of knowledge. A comprehensive systematic literature review was utilised to screen, select, and organise the literature written on the theories behind MA from 2014 to 2024. The aim was to identify and rank the theories regarding MA. The findings indicated that most articles referred to critical race theory, followed by social identity theory and social domain theory when explaining the existence of MAs. Most theories focused on explaining racial MAs. Based on the findings of this research, the most valuable contribution to the body of knowledge could be made by adding to critical race theory. However, as explaining MA was not solely race-related, a collective view that includes social identity theory and social domain theory could provide a theoretical framework for future empirical research.